RESEARCH OF VIBRATION MECHANOCHEMICAL ZINC COATING MICRO/NANO-PROFILE - Anatoly P. Babichev; Vladimir V. Ivanov; Sergey N. Khudoley (Advanced Engineering Research, 2011)
The research results of the micro/nano-profile of the vibration mechanochemical zinc coating are presented.